Intimate partner violence in Greece: a study of 664 consecutive forensic clinical examinations. (17th May 2020) - Katsos, Konstantinos; Sakelliadis, Emmanouil I; Zorba, Eleni; Tsitsika, Artemis; Papadodima, Stavroula; Spiliopoulou, Chara
Abstract: Background: Intimate partner violence (IPV) is a well-known phenomenon, which affects mostly women. While IPV victims may attend emergency departments (EDs) seeking medical care, not all of them will make an allegation against their abusers. Objective: The aim of this study was to examine the prevalence and the characteristics of the victims, who had made an allegation about the violent incident and had been examined by a forensic pathologist for judicial purposes, and had attended EDs seeking medical care, before the forensic examination. Methods: We reviewed the archives of clinical examinations that were conducted at the Department of Forensic Medicine and Toxicology of National and Kapodistrian University of Athens during a 5-year period (2012–16). Results: Six hundred sixty-four clinical examinations were conducted at our Department for IPV allegations. According to our findings, women were more likely to seek medical care than men. Victims who have attended EDs were more likely to have sustained injuries located at least on the head or on the lower limbs. Conclusion: The majority of IPV victims in the broader region of Attica (Greece) were women, usually married, and aged between 30 and 49 years old. Despite the fact that the majority of IPV incidents are not reported to police, every person who is engaged in the process of dealing with IPV victims has to be educated and adequately informed about this phenomenon, its implications and the possible ways to deal with it. Furthermore, victims need to be educated and informed adequately in waiting rooms of EDs.